Determining Optimal Measurement Time Points for SPAD and Canopy Temperature in Drought Tolerant Cotton (Gossypium hirsutum L.) Breeding - GÖREN, Hatice Kübra (ISPEC Tarım Bilimleri Dergisi, 2024)
This study investigates optimal physiological parameter measurement times in Gossypium hirsutum L. to assess the effects of drought stress. Observations of SPAD (Leaf Chlorophyll Content) and canopy temperature depression (CMD) were made at different growth stages, including Early Growth, Flowering, Bolling, and Boll Opening stages. These measurements were linked to yield and fiber quality parameters across the cotton grown stages.Data was analyzed using Principal Component Analysis (PCA) to uncover complex trait variations and genetic diversity under water-limited conditions. Specifically, PCA revealed significant variations in key traits such as yield and fiber quality under water stress conditions.Canopy temperature measurements highlighted the reliability of assessments made during specific stages, particularly the Bolling stage, for evaluating trait relationships.Leaf chlorophyll content (SPAD) analysis emphasized the significant correlation of SPAD4 with fiber elongation (FE) and lint percentage (LP).Overall, the results demonstrate the critical importance of timely SPAD and CMD measurements, especially during the Bolling stage (SPAD3 and CHD3), for understanding cotton traits under drought stress.These findings underscore the importance of strategic physiological parameter assessments in cotton breeding under challenging environmental conditions.